D'une rive à l'autre : circulations et échanges entre la Mauretanie Césarienne et le sud-est de l'Hispanie (antiquité-moyen-âge) - Amraoui, Touatia,; Quevedo, Alejandro, (Archaeology of the Maghreb ;, 2022)
Algeria is largely open to the western Mediterranean, but links with its neighbouring regions are poorly understood. This book considers networks between Algeria and the south-east of the Iberian Peninsula, from pre-Roman times to the Middle Ages. Papers revolve around three themes: mobility; economic exchange; and cultural and knowledge transfer.